A case series of patients with cardiac amyloidosis evaluated at a Colombian university hospital - López-Ponce de León, Juan David; Granados-Álvarez, Santiago; Arango-Ibanez, Juan Pablo; Montero Echeverri, Juan Manuel; Arteaga Tobar, Andrea Alejandra; Garcia, Andrea Facio-Lince; Rodas Cortes, Yorlany; Gómez-Mesa, Juan Esteban (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn Colombia, the characteristics of cardiac amyloidosis (CA)—including wild-type transthyretin amyloidosis (ATTRwt), immunoglobulin light chain amyloidosis (AL), and genetic variant transthyretin amyloidosis (ATTRv)—are underexplored.MethodsThis case series at a Colombian university hospital analyzed demographic, clinical, laboratory, radiological, and genetic data of CA patients diagnosed between 2018 and 2022. Patients with incomplete data underwent further testing.ResultsOf 24 identified patients, 14 were included after exclusions. The majority were male (73.3%), with an average age of 70.6 years. ATTRv and AL were equally prevalent (42.8%), followed by ATTRwt (14.2%). The p.Val142Ile TTR mutation was found among all ATTRv patients. Most presented with functional capacity NYHA I-II and common electrocardiographic findings included low voltage, atrial fibrillation, and first-degree AV block. Echocardiography and cardiac magnetic resonance imaging revealed ventricular hypertrophy, diastolic dysfunction, reduced longitudinal strain, and late myocardial enhancement.ConclusionsAL and ATTRv were the most common causes of CA followed by ATTRwt. This distribution, along with the clinical, and radiological characterization is consistent with previous reports of other regions. The p.Val142Ile mutation was the only one found in patients with ATTRv, suggesting a strong African genetic influence. These findings enhance our understanding of CA in the region.